Habitat and Marine Reserve Status Drive Reef Fish Biomass and Functional Diversity in the Largest South Atlantic Coral Reef System (Abrolhos, Brazil) - Rolim, Fernanda Andreoli; Langlois, Tim; Motta, Fábio dos Santos; Castro, Guilherme Malagutti de; Lester, Emily; Abieri, Maria Luiza; Gadig, Otto Bismarck Fazzano; Moura, Rodrigo Leão de (Frontiers in Marine Science, 2022)
The effects of fishing have been documented across coral reefs worldwide. No-take marine reserves do not only act as a conservation tool but also allow an opportunity to study impacts of fishing, by acting as control sites. In addition, well-planned and well-managed no-take marine reserves (NTRs) provide conservation benefits that are essential to marine biodiversity and ecosystem-based management. The Abrolhos Marine National Park, off the tropical Brazilian coast, protects part of the largest coral reef system in the South Atlantic. To investigate the effects of fishing on reef fish richness, abundance, biomass, and functional diversity of the fish assemblage, we compared sites across two protection levels considering the variation in habitats (Fringing Reefs—Protected; Pinnacles Reefs—Protected; and Coastal Reefs—Open Access), using Baited Remote Underwater Stereo-Video systems (stereo-BRUVs). We adjusted generalized additive mixed models of fish assemblage characteristics with protection levels and environmental variables, such as topographic complexity (mean relief and relief variation), visibility, and benthic cover percentage. Inside NTRs, we found higher total biomass and biomass of fishery target species and carnivores, specifically for the Carcharhinidae (sharks) and Epinephelidae (groupers) families, indicating direct fisheries effects on these groups. In contrast, the ecological parameters of non-target fish were positively correlated with habitat characteristics, including mean relief and variance of relief. Moreover, fish functional diversity was higher within NTRs, demonstrating an even distribution of functional entities. The presence of large mobile predators and the overall higher biomass of carnivores inside the NTR indicate the effect of fishing exclusion. Our results point to the value of NTRs to study the effects of fishing and achieve biodiversity conservation and suggest the importance of using remote sampling methods to assess large mobile predators.